Abnormal Expression of BTLA and CTLA-4 Immune Checkpoint Molecules in Chronic Lymphocytic Leukemia Patients. (28th July 2020) - Karabon, L.; Partyka, A.; Ciszak, L.; Pawlak-Adamska, E.; Tomkiewicz, A.; Bojarska-Junak, A.; Roliński, J.; Wołowiec, D.; Wrobel, T.; Frydecka, I.; Kosmaczewska, A.
Abstract : Chronic lymphocytic leukemia (CLL) is characterized by the peripheral accumulation of neoplastic B cells and is frequently complicated by the systemic immunosuppression associated with an impairment in B and T lymphocyte activation. We hypothesized that the expression of immune checkpoint suppressors B and T lymphocyte attenuator (BTLA) and cytotoxic T lymphocyte antigen (CTLA-4) is disturbed in both lymphocyte subpopulations in CLL. The expression of CTLA-4 and BTLA mRNA was determined by real-time PCR, while CTLA-4 protein expression (surface or intracellular) was estimated in BTLA+ lymphocytes by flow cytometry. In CLL patients, we observed a higher gene transcript level of BTLA and CTLA-4 than in healthy individuals in both freshly isolated and PMA stimulated B and T cells. Remarkably, lower amounts of both inhibitory proteins were found in peripheral blood (PB) CLL B cells, whereas normal BTLA and elevated CTLA-4 were found in T cells. Consistently, there was a prevalence of CTLA-4+ cells within circulating BTLA+ T cells cells of patients confronting PB healthy cells. After in vitro stimulation, the only change found in CLL patients was a decrease in BTLA expression in B and T lymphocytes. In contrast, healthy lymphocytes responded more vigorously as regards the BTLA and CTLA expression with substantially higher frequency of CD69+ cells under the stimulating condition compared to corresponding cells from the CLL group. Our results indicate that CLL development is associated with the affected expression of BTLA and CTLA-4 checkpoint receptors in PB and its impaired expression might be associated with lowering of the threshold for B cell activation and proliferation, while upregulated CTLA-4 expression in CLL peripheral BTLA+ T cells may contribute to suppressed T cell effector functions. This hypothesis needs to be validated in future studies, which would allow us to explain how the increased or decreased expression of these molecules affects the cell function.